Pengaruh Penggunaan Media Audio Visual Menggunakan Video Animasi Untuk Meningkatkan Kosakata Di Taman Kanak-Kanak Pusat Padu Lino - Wina; Muhammad Akil Musi; Rusmayadi; Rika Kurnia R; Dzulfadhilah, Fitriani (Program Studi Pendidikan Islam Anak Usia Dini, 2023)
Based on the search conducted, there are 12 children whose vocabulary mastery has not developed optimally, it can be seen when the teacher asks about color problems. Children do not understand the essence of the questions given, for example when children are asked questions about the color of roses there are children who answer red, white, yellow and there are children who do not answer at all. This study aims to see the effect of audiovisual media through animated videos to improve vocabulary in kindergarten Pusat Padu Lino Tanah Towa Kajang Bulukumba Regency. The research method used is quantitative with a quasi-experimental type. The population was 19 children in the kindergarten of Pusat Padu Lino Tanah Towa Kajang Bulukumba Regency. Sampling was done by purposive sampling technique. The research sample was 12 children, namely 6 children in the control group and 6 children in the experimental group. Descriptive data analysis technique and non-parametric statistical analysis, namely the Wilcoxon sign rank test. The results showed that the experimental group experienced an average increase of 24.67 and the control group of 21.00. The significant value can be seen in the experimental group test results, namely (2-tailed), 0.027 <0.05, namely H0 is rejected and H1 is accepted. Therefore, it can be concluded that the use of audio-visual media using animated videos can provide an increase in children's vocabulary at TK Pusat Padu Lino Tanah Towa Kajang Bulukumba Regency.